El proceso de cantonización de Chambo desde la memoria colectiva - Quiguiri Jatzatza, Dorian Alexis (2024)
The following research work had the objective of analyzing the process of cantonization of Chambo applying the collective memory. The research methodology is of qualitative approach. The type of research is mixed where I use two types and they are geographical and historical research, each of them contributed to build my research work and to be as concrete as possible. The research design that I apply is explanatory, which is used in order to understand the causes and effects of a specific phenomenon. The tools used were in-depth interviews, direct observation, and review of bibliographic sources, which were very helpful in constructing the document by applying the individual memory of the people who lived in this historical monument and transforming the collective memory into a compilation of information. The results obtained in the process of cantonization of Chambo was given on March 18, 1988 in the government of President Leon Febres Cordero Rivadeneira. The president was Dr. Fernando Guerrero Guerrero, vice president of the National Assembly in which he served for that day as president in charge of the assembly. He determined in the act referring to the process of cantonization that the Chambo parish belonging to the province of Chimborazo has had an accelerated development in all aspects of urbanism, population, agriculture and commerce that the said parish has enough personnel properly trained to carry out the administrative process of the new canton (law 84, 1988).